Transforming Indigenous Mindsets: The Impact of Floating Nature Schools on Suku Anak Dalam Education - Sinta Nurjulaiha; Junaidi Irwandi; Susi Fitria Dewi; Yurni Suasti (AL-ISHLAH: Jurnal Pendidikan, 2025)
Indigenous communities such as the Suku Anak Dalam (SAD) in South Sumatra have historically viewed formal education as irrelevant or even threatening to their cultural identity. This study investigates how non-formal, culturally responsive education—delivered through a "floating nature school"—can transform such perceptions. A qualitative descriptive approach was employed, using purposive sampling to select participants from the floating nature school in Muara Medak. Data were gathered through classroom observations, semi-structured interviews with students and teachers, and supporting documentation. Triangulation was used to ensure the validity of findings. The study reveals a gradual shift in SAD students’ mindsets from a fixed to a growth orientation. Initially, education was seen as unnecessary for forest-based life. However, the school’s culturally adapted curriculum—integrating local knowledge, literacy, hygiene, and life skills—helped reframe education as valuable and empowering. Students began to demonstrate enthusiasm for learning, improved self-confidence, and aspirations for future careers. Independence in daily decision-making and personal responsibility also increased. Despite structural limitations and occasional irregular attendance, the floating nature school serves as a bridge between tradition and modernity. It successfully aligns educational content with SAD cultural values, fostering both skill development and cultural resilience. Contextualized, community-based education can significantly reshape Indigenous mindsets toward schooling, positioning education not as a threat, but as a tool for self-determination and improved quality of life.